Mechatronics in medicine : a biomedical engineering approach - Najjariyan, Siyamik (New York : McGraw-Hill, 2012)
'Comprehensive coverage of mechatronics in medical systems. Mechatronics in Medicine: A Biomedical Engineering Approach addresses this emerging field focused on areas of medicine such as robotic surgery and smart surgical instruments, design of artificial organs, new medical imaging systems, and novel diagnostic and therapeutic systems. This pioneering work addresses the development of computer-controlled mechanical devices for use in a wide variety of areas in biomedicine. Mechatronics in Medicine: A Biomedical Engineering Approach offers a basic background in mechatronics. Covers multidisciplinary medical systems, discusses design and operation of biomechatronics systems Includes details on state-of-the-art technologies; cutting-edge coverage introduction to mechatronics; sensing technology; actuators and feedback sensors; mechanisms and mechanical Devices; processing and control Systems; expert systems; medical imaging; applications of mechatronics in medicine; medical case studies in mechatronics'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Biomedical engineering; Computing Methodologies; Diagnosis, Computer-Assisted -- instrumentation; Electrical Equipment and Supplies; Mechanical Processes; Therapy, Computer-Assisted -- instrumentation